2011
DOI: 10.1590/s1806-66902011000400011
|View full text |Cite
|
Sign up to set email alerts
|

Diversidade genética de acessos de feijão comum por caracteres agronômicos

Abstract: Resumo -Este experimento teve como objetivo avaliar a divergência genética entre 57 acessos de feijão comum, sendo 31 genótipos locais do sul do Espírito Santo, 20 da EMBRAPA e seis cultivares comerciais. Foram realizados três experimentos no município de Alegre, ES nos anos agrícolas de 2008/2009 e de 2009/2010. O delineamento utilizado foi o de blocos casualizados com três repetições. Os dados foram submetidos à análise de variância pelo teste F. Foi utilizada análise multivariada para avaliar a divergência … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
16
0
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 15 publications
10
16
0
11
Order By: Relevance
“…Therefore, the agronomic performance of the common bean genotypes was not the same for both growing seasons, corroborating with previous studies reported by Cabral et al (2011), Moura et al (2013), Ribeiro et al (2014), and Mambrin et al (2015). Preliminary studies also found a significant genotype x environment interaction for zinc concentration in grains of common bean genotypes (Silva et al, 2012;Hossain et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, the agronomic performance of the common bean genotypes was not the same for both growing seasons, corroborating with previous studies reported by Cabral et al (2011), Moura et al (2013), Ribeiro et al (2014), and Mambrin et al (2015). Preliminary studies also found a significant genotype x environment interaction for zinc concentration in grains of common bean genotypes (Silva et al, 2012;Hossain et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…Adotou-se o delineamento de blocos ao acaso, com três repetições, onde as parcelas experimentais foram compostas de quatro fileiras de 4m de comprimento, com espaçamento de 0,5m e densidade de semeadura de 10 sementes por metro, de acordo com CABRAL et al (2011), analisando apenas a área útil.…”
Section: Methodsunclassified
“…Because of the importance for crop improvement, studies on the genetic diversity have been carried out in different crops such as guava (Pessanha et al, 2011), common bean (Cabral et al, 2011) and coffee (Martins et al, 2016). A number of genetic divergence studies have also been carried out with different accessions of papaya (Carica papaya L.) (Ramos et al, 2011;Quintal et al, 2012;Oliveira et al, 2011;Lucena and Dantas, 2015).…”
Section: Introductionmentioning
confidence: 99%